Religious Moderation: Identity Politics, Policy, and Social Change in Islamic Religious Colleges - Miftah, Muhammad; Sutrisno, Sutrisno; Daulay, Hamdan (LPPM IAIN Kudus, 2023)
Religious moderation is politically included in public policies that are integrated into the 2020-2024 National Medium-Term Development Plan (Rencana Pembangunan Jangka Menengah Nasional, RPJMN). Ministry of Religion as the leading sector for mainstreaming religious moderation in its environment has the responsibility to translate religious moderation from the narrative of religious moderation to the real action in its institutional units. This research is qualitative research conducted at State Islamic University (Universitas Islam Negeri, UIN) Walisongo Semarang which seriously promotes religious moderation in the institution. The results of this study are the problem of strengthening identity politics as one of the main causes of religious extremism and social change that exist, one of the efforts to minimize social turmoil in UIN Walisongo is by instilling the values of religious moderation through the tri dharma of university, namely teaching, research, and community service. The aspect of locality is the main capital in implementing religious moderation at UIN Walisongo. Indigenous religiosity combines religion and locality with a theo-anthropocentric approach, exploring cultural values in order to strengthen religion in the implementation aspect. The impact of the implementation of the data religious moderation policy is seen from the realm of ideality of policy content in the religious moderation policy, which can be seen from the integration of relations or a harmonious relationship between individual elements and social elements in human interaction which is the main target in the religious moderation policy promoted by the Ministry of Religion.